2018
DOI: 10.1002/jum.14838
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Quantitative Uterine Fibroid Perfusion Parameters From Contrast‐Enhanced Ultrasound for the Therapeutic Effect of High‐Intensity Focused Ultrasound Ablation

Abstract: Objectives To assess the predictive significance of quantitative perfusion parameters from contrast‐enhanced ultrasound (CEUS) for the therapeutic response to high‐intensity focused ultrasound (HIFU) ablation in patients with uterine fibroids. Methods A total of 263 patients with single uterine fibroids were treated with HIFU ablation under ultrasound guidance. The arrival time, peak time, enhancement time, enhancement intensity, and enhancement rate were evaluated with pretreatment CEUS. According to a nonper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Studies have shown that blood flow in vessels feeding the target tissue can disperse US energy and affect heat deposition . For PHIFU at a lower DC to achieve the same effective irradiation time as CHIFU, an increase in the total irradiation time is required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that blood flow in vessels feeding the target tissue can disperse US energy and affect heat deposition . For PHIFU at a lower DC to achieve the same effective irradiation time as CHIFU, an increase in the total irradiation time is required.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported the potential utility of CEUS during or immediately after a UAE procedure 17–19 . A recent study in China demonstrated the utility of quantitative parameters from CEUS for evaluating the therapeutic effect of high‐intensity focused US ablation of fibroids 20 . However, none of these studies compared CEUS to MR, which is the reference standard diagnostic tool for uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS for monitoring ablation therapies. The predictive value of quantitative perfusion parameters obtained by CEUS for the therapeutic response to HIFU was assessed by Wang et al 39 They showed that fibroids with lower perfusion time parameters and higher intensity parameters, that is, "quickrise-quick-decline" blood flow profile, had poor ablation efficacy. Table 4 provides an overview of the studies using CEUS pre-and post-treatment to image changes in perfusion.…”
Section: Monitoring and Enhancing Effectiveness Of Minimally Invasive Therapiesmentioning
confidence: 99%
“…The side-effects were transient and disappeared 1 to 4 hours post-procedure, all pain scores were mild (<4). 20,[27][28][29][30][31][32][33][34][35][36][37][38][39]41,[43][44][45][46][47][48]55 The differences in side-effects between "HIFU" and "HIFU + CEUS" are listed in Supplemental Appendix B.…”
Section: Contrast Agents and Adverse Eventsmentioning
confidence: 99%